2016
DOI: 10.1007/s00384-016-2633-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences between colon and rectal cancer in complications, short-term survival and recurrences

Abstract: PurposeMany apparent differences exist in aetiology, genetics, anatomy and treatment response between colon cancer (CC) and rectal cancer (RC). This study examines the differences in patient characteristics, prevalence of complications and their effect on short-term survival, long-term survival and the rate of recurrence between RC and CC.MethodsFor all stage II–III CC and RC patients who underwent resection with curative intent (2006–2008) in five hospitals in the Netherlands, occurrence of complications, cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 29 publications
4
67
2
1
Order By: Relevance
“…We did not find any significant overall difference in recurrence rates between colon and rectal cancers, which is in contrast to a pervious Dutch study [9].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We did not find any significant overall difference in recurrence rates between colon and rectal cancers, which is in contrast to a pervious Dutch study [9].…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have identified several possible additional factors associated with recurrence. Patient factors, like intake of coffee and alcohol, smoking, weight-loss and Glascow Prognostic score [2] [3] [4] [5] [6], treatment factors like surgical experience and technique [7] [8], tumor factors like location, differentiation, vein-, nerve-and lymphatic ingrowth [9] [10] and molecular factors [11] [12] [13] [14] have been shown to influence cancer recurrence, and adjuvant oncological therapy is often recommended. In the present study, we have taken interest in what consequences repeated or aggravated inflammatory stress will inflict on the patient and influence the risk of recurrence after potential curative resection of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it therefore seems appropriate to analyse treatment outcomes separately. Many studies have found that SSI occurs more frequently in rectal cancer patients undergoing surgery than in those being operated for colonic cancer [11][12][13][14]17]. A study by Konishi et al on 556 patients after large bowel resection found that in those post-rectal resection, SSI occurred twice more frequently compared to patients who had undergone colonic resection, (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a lower survival among colon cancer patients because of a more severe effect of complications compared with patients with rectal cancer (van der Sijp et al, 2016).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Several studies have shown genetic, morphological, and clinical differences, as well as differences in survival between cancers of the colon and rectum (Kornmann et al, 2013, van der Sijp et al, 2016 suggesting that CRC might consist of two separate entities. As an example Kornmann et al showed an improved survival in treated patients with colon cancer but not among patients with rectum…”
Section: Colorectal Cancermentioning
confidence: 99%